Evaluating Deterrence Incentives across Legal Systems: Effects of Changing the Basis for Measuring Exposure - Smith, Michael L. (Assurances et gestion des risques / Insurance and Risk Management, 2004)
In the area of motor vehicle safety, legislators and public officials often rely on statistical measures to evaluate the effect of road design on safety or to evaluate legal and financial incentives for drivers to avoid accidents. The evidence used for evaluation typically takes the form of a rate such as a death rate per vehicle-mile, where the denominator of the rate reflects a measure of exposure. This paper shows how the basis for measuring exposure can affect such comparisons. Although this principle applies to any evaluation involving alternative measures of exposure, the empirical tests in this paper focus on the origin of countries’ legal systems. The tests show that fatality rates from motor vehicle accidents vary significantly across countries classified by origin of legal System, although rankings of legal systems can depend on whether fatality rates are measured relative to population, vehicle count, or a basis combining population and vehicle count. Despite evidence of differences between legal Systems that persist over time, rankings also can depend on the time period from which data are drawn. The paper also illustrates how supplemental data can be used to reconcile discrepancies occurring when different measures of exposure are employed.